Factors Affecting Completeness Basic Immunization Village District of North Krembangan - Adzaniyah Isyani Rahmawati; Chatarina Umbul Wahjuni (Universitas Airlangga, 2014)
Basic immunization is one way to prevent and manage infectious diseases. This study was conducted to analyze the factors that influence the completeness of basic immunization in infants or toddlers in North Krembangan District, Surabaya as prevention of vaccine preventable diseases. The design of the study used a case-control study with a total sample of 22 respondents and a total of 44 respondents. The research subjects were taken by simple random sampling. The variables studied in this study were the respondent's age, level of education, income level, employment status, knowledge about immunization, traditions and beliefs, and family support, attendance, location of immunization and attitude of officers. The results of this study indicate the completeness of immunization status is influenced by tradition (p = 0.015) and family support (p = 0.001). The completeness of basic immunization in toddlers as an effort to prevent vaccine preventable diseases is influenced by family traditions that are accustomed to giving immunizations to infants or their toddlers having a baby chance or their toddlers will get complete immunizations and families who support infant immunization or their toddlers have the opportunity to get complete immunizations. Researchers suggest that there needs to be an approach to health promotion to the community in order to change the tradition of not being accustomed to giving immunizations to being supportive for giving immunizations and giving understanding to family decision-makers that immunization benefits for the infants or toddler.